On the relationship between climate and homelessness - Kevin C. Corinth; David S. Lucas (American Enterprise Institute (AEI), 2017)
Corinth and Lucas look the relationship between climate and homelessness. They find that cold places uniformly have low rates of unsheltered homelessness, while warm places display wide variation.
Keywords: A; 330; homelessness; Climate change